Analysis of the Influence of Motor Development on Children's Speech Language Ability - Lailatul Izzah; Renny Rahmalia; Eva Yuliza; Raspan Hamdi (Program Studi Psikologi Islam, 2024)
The aim of this research is to determine the percentage of the contribution of motor development to children's speech-language abilities. This research involved 23 typical preschool-age children. Each child's motor and speech-language abilities were measured using the Developmental Profile instrument. Based on statistical analysis, it was found that the influence of motor skills on speech language abilities was 18.7%, while 81.3% of speech language abilities were influenced by variables other than motor skills. This study reveals that there is an influence between motor skills and children's speech-language abilities. This study has limitations in terms of sample size, so this may influence the results of this research. Therefore, a representative sample that can represent the population in Indonesia is needed for further studies. However, this could be an important initial study in a country where research on this subject has traditionally been limited.